HTTPS approach to resist MITM attack in secure SMS - Khan, Muhammad Murad (2013)
Short Messaging Service has become vital part of every individuals life. Like human, businesses have also gained benefit from SMS by providing business alerts, transaction services, resource management etc over it using Automated SMS. With exchange of confidential and mission critical information over SMS, security of SMS has become a big concern. Many researchers provided solutions to secure content of message using encryption but key exchange of encryption algorithm cannot be secured. Man In The Middle can observe key exchange messages and can setup MITM attack between communication. Security vulnerability inside this operation is that, secret key and encrypted messages are shared over same channel i.e. SMS. This project propose a PKI web system that distributes encryption keys for encryption of SMS over HTTPS, making MITM attack near to impossible on Secure SMS.